FALLING STANDARD OF EDUCATION A CASE OF EKITI STATE COLLEGE OF EDUCATION - Borisade Tunde Fidelis (European Scientific Journal, ESJ, 2013)
This study examined the position of the standard of Education in Ekiti State College of Education. Two periods of an interval of ten years, consisted of three academic sessions each, were used for the study-a period of 1999, 2000, 2001 and a period of 2009, 2010, 2011. The academic performance of students during the two periods were compared and analysed. The result of the findings showed that there was a significant difference in the academic performance of students between the two study periods taken together, and a significant difference between each study year of ten years interval. Based on the findings, it was discovered that lecturers, students societal ills, overloaded curriculum were the responsible factors. It was thus recommended that lecturers welfare, adequate fundings, provision of infrastructures, prompt payment of retired staff gratuities and review of overloaded curricula will go a longway at improving the standard of education in the study area and beyond.